IMPLEMENTATION OF MISSING VALUES HANDLING METHOD FOR EVALUATING THE SYSTEM/COMPONENT MAINTENANCE HISTORICAL DATA - Entin Hartini (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2017)
Missing values are problems in data evaluation. Missing values analysis can resolve the problem of incomplete data that is not stored properly. The missing data can reduce the precision of calculation, since the amount of information is incomplete. The purpose of this study is to implement missing values handling method for systems/components maintenance historical data evaluation in RSG GAS. Statistical methods, such as listwise deletion and mean substitution, and machine learning (KNNI), were used to determine the missing data that correspond to the systems/components maintenance historical data. Mean substitution and KNNI methods were chosen since those methods do not require the formation of predictive models for each item which is experiencing missing data. Implementation of missing data analysis on systems/components maintenance data using KNNI method results in the smallest RMSE value. The result shows that KNNI method is the best method to handle missing value compared with listwise deletion or mean substitution.Keywords: missing value, data evaluation, alghorithm, implementation IMPLEMENTASI METODE PENANGANAN DATA HILANG  UNTUK MENGEVALUASI DATA SEJARAH PERAWATAN SISTEM/KOMPONEN. Data hilang merupakan masalah dalam melakukan evaluasi data. Analisis data hilang dapat menyelesaikan permasalahan ketidaklengkapan data yang tidak tersimpan dengan baik. Data yang hilang akan memperkecil presisi dari perhitungan, dikarenakan jumlah informasi yang tidak lengkap. Tujuan dari penelitian ini adalah implementasi  metode penanganan data hilang untuk evaluasi data sejarah perawatan sistem/komponen RSG GAS. Metodologi yang digunakan untuk menentukan data hilang yang berhubungan dengan data sejarah perawatan sistem/komponen adalah statistics, listwise deletion dan mean substitution, dan machine learning (KNNI). Metode mean substitution dan KNNI dipilih karena metode ini tidak memerlukan informasi untuk pembentukan model prediksi untuk setiap item yang mengandung data hilang. Implementasi analisis data hilang pada data perawatan sistem/komponen menggunakan metode KNNI menghasilkan nilai RMSE terkecil. Hasil ini menunjukan bahwa metode KNNI merupakan metode terbaik untuk menangani data hilang dibanding dengan listwise deletion atau mean substitution.Kata kunci: data hilang, evaluasi data, algoritma, implementasi